2018
DOI: 10.1111/mmi.14169
|View full text |Cite
|
Sign up to set email alerts
|

The antibiotic action of methylarsenite is an emergent property of microbial communities

Abstract: Arsenic is the most ubiquitous environmental toxin.Here, we demonstrate that bacteria have evolved the ability to use arsenic to gain a competitive advantage over other bacteria at least twice. Microbes generate toxic methylarsenite (MAs(III)) by methylation of arsenite (As(III)) or reduction of methylarsenate (MAs(V)). MAs(III) is oxidized aerobically to MAs(V), making methylation a detoxification process. MAs(V) is continually re-reduced to MAs(III) by other community members, giving them a competitive advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 34 publications
2
69
0
Order By: Relevance
“…To date, more and more bacterial strains have been identified that are capable of reducing MAs(V), including the environmental isolate Burkholderia sp. MR1, P. putida KT2440, S. putrefaciens 200, and Sinorhizobium meliloti RM1021 (Chen et al, 2019b). However, the genes/enzymes involved in MAs(V) reduction have still not been identified.…”
Section: Environmental Prevalence Of Organoarsenicals Simple Methylarmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, more and more bacterial strains have been identified that are capable of reducing MAs(V), including the environmental isolate Burkholderia sp. MR1, P. putida KT2440, S. putrefaciens 200, and Sinorhizobium meliloti RM1021 (Chen et al, 2019b). However, the genes/enzymes involved in MAs(V) reduction have still not been identified.…”
Section: Environmental Prevalence Of Organoarsenicals Simple Methylarmentioning
confidence: 99%
“…Like most antibiotics, it would have required a way to get out the cells of the producer, and the ArsP MAs(III) efflux permease also appears to have evolved prior to the GOE. Other bacteria acquired the arsP gene and became resistant to MAs(III) -an early example of antibiotic resistance (Chen et al, 2019b). Although cells with arsM would also have produced DMAs(III), when arsP is co-expressed, it extrudes MAs(III) before it can be methylated a second time (Chen et al, 2019b), so the more stable MAs(III) would have been the major species with antibiotic activity.…”
Section: Enzymes and Transporters Of Methylarsenical Biotransformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to utilize As(III) or As(V) for energy generation would provide a distinct advantage. Furthermore, production of a toxin such as MAs(III) by even a low abundance organism could have devastating effects on microbiome neighbours that lack the ability to eliminate it from the cell (ArsP) or detoxify it (ArsI or ArsH) (Chen et al, 2018). Production of arsenic-based antibiotics such as arsinothricin (Kuramata et al, 2016) could have similar effects, though moderated by ArsN that inactivates it (Nadar et al, 2019) and arsenic resistance acquired from spontaneous mutations in vivo will also account for some changes.…”
Section: Arsenic Perturbation Of the Microbiomementioning
confidence: 99%